Research on the Virtualized Core Network - Xiaojuan Hu; Huiling Zhao (Dianxin kexue)
Scenarios of virtualized core network were analyzed firstly, then virtualized core network architecture and related key technologies were discussed. Finally, the core network virtualization processes and procedures were forecasted.